Assessing the Role of Age, Education, Gender and Income on the Digital Divide - Elena-Bucea, Anca (2022)
Elena-Bucea, A., Cruz-Jesus, F., Oliveira, T., & Coelho, P. S. (2021). Assessing the Role of Age, Education, Gender and Income on the Digital Divide: Evidence for the European Union. Information Systems Frontiers, 21(4), 1007–1021. [Adavanced online publication on 19 May 2020]. https://doi.org/10.1007/s10796-020-10012-9